Marginal Costs and Likely Supply Elasticities for Pollination and Honey. (27th August 2019) - Champetier, Antoine; Sumner, Daniel A.
Abstract: We report new estimates of beekeeper costs and revenues, which include major activities undertaken by beekeepers, including honey producers and pollinators. We use our cost estimates, recent government surveys and other United States Department of Agriculture information to characterize supply functions for (1) pollination services to crops that bloom in the late winter (dominated by almonds), (2) pollination services to crops that bloom in the spring and summer, and (3) honey produced in the United States. The positions and shapes of these supply functions are crucial to understanding how the honeybee industry will respond to changes in demand for pollination services and other market conditions, including shifts in honey demand, honey import supply, and forage availability affected by climate change.